Role of IME1 expression in regulation of meiosis in Saccharomyces cerevisiae. - Smith, H E (1990)
Two signals are required for meiosis and spore formation in the yeast Saccharomyces cerevisiae: starvation and the MAT products a1 and alpha 2, which determine the a/alpha cell type. These signals lead to increased expression of the IME1 (inducer of meiosis) gene, which is required for sporulation and sporulation-specific gene expression. We report here the sequence of the IME1 gene and the consequences of IME1 expression from the GAL1 promoter. The deduced IME1 product is a 360-amino-acid protein with a tyrosine-rich C-terminal region. Expression of PGAL1-IME1 in vegetative a/alpha cells led to moderate accumulation of four early sporulation-specific transcripts (IME2, SPO11, SPO13, and HOP1); the transcripts accumulated 3- to 10-fold more after starvation. Two sporulation-specific transcripts normally expressed later (SPS1 and SPS2) did not accumulate until PGAL1-IME1 strains were starved, and the intact IME1 gene was not activated by PGAL1-IME1 expression. In a or alpha cells, which lack alpha 2 or a1, expression of PGAL1-IME1 led to the same pattern of IME2 and SPO13 expression as in a/alpha cells, as measured with ime2::lacZ and spo13::lacZ fusions. Thus, in wild-type strains, the increased expression of IME1 in starved a/alpha cells can account entirely for cell type control, but only partially for nutritional control, of early sporulation-specific gene expression. PGAL1-IME1 expression did not cause growing cells to sporulate but permitted efficient sporulation of amino acid-limited cells, which otherwise sporulated poorly. We suggest that IME1 acts primarily as a positive regulator of early sporulation-specific genes and that growth arrest is an independent prerequisite for execution of the sporulation program.